Smart Mobile Application for Decision Support Systems on Determination of Resident in Dormitory - Achmad Jauhari; Fifin Ayu Mufarroha; Muhammad Amfahtori Wijarnoko; Moh. Yusril Ihza Maulana; Ahmad Try Bayu Al Haq; Linawati Linawati (Jurnal Ilmiah Kursor, 2020)
The dormitory is one of the facilities provided with the aim of helping students to get a place to live because some of them come from distant places. The Trunojoyo Madura University dormitory has regulations that serve as a place for the process of character education, spiritual deepening, moral improvement. With these regulations, plus the boarding house is a conducive, economical, and strategic place to stay making many students interested in being able to live there. The problem is that each semester change is carried out by the selection of dorm residents and so far it is still done manually by way of discussion of each individual. Therefore, the purpose of this research is to help the board by building a decision support system in determining residents who are still eligible to live in a dormitory and provide opportunities for other students to live in a dormitory. We develop systems based on mobile applications. TOPSIS method (Technique for Order of Preference by Similarity to Ideal Solution) is implemented as a multi criteria decision making method with four main criteria including routine absence, non-routine absence, violation and notes. The final results of this decision support system are ranks and colors that indicate the status of boarding residents. Ranking starts from the top (1) to the bottom (216) accompanied by a status of green to red. The color status is divided into 3 namely green (safe), yellow (vulnerable), and red (issued). From 216 boarders we took 10 samples of dormitory data for testing. The results of trials with 10 data samples by applying the TOPSIS method obtained an accuracy of 90%.